2018
DOI: 10.1016/j.plaphy.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Age-related mechanism and its relationship with secondary metabolism and abscisic acid in Aristotelia chilensis plants subjected to drought stress

Abstract: Drought stress is the most important stress factor for plants, being the main cause of agricultural crop loss in the world. Plants have developed complex mechanisms for preventing water loss and oxidative stress such as synthesis of abscisic acid (ABA) and non-enzymatic antioxidant compounds such as anthocyanins, which might help plants to cope with abiotic stress as antioxidants and for scavenging reactive oxygen species. A. chilensis (Mol.) is a pioneer species, colonizing and growing on stressed and disturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 72 publications
2
41
0
3
Order By: Relevance
“…Micropropagated in‐vitro Maqui plants ( A. chilensis ) donated by BestPlant Co. (Curicó, Chile) were used in this study. One‐year‐old plants were transplanted to 2 l pots with Andisol soil and acclimated in a greenhouse (temperature: 25 ± 3°C; photoperiod: light 16/8 h dark; humidity: 60–70%; and a mean photosynthetic active radiation at midday of 300 μmol m −2 s −1 ) for 2 weeks as described previously in González‐Villagra et al (). Plants were then divided into two groups (20 plants for each group): daily irrigated (DI) and non‐irrigated (NI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Micropropagated in‐vitro Maqui plants ( A. chilensis ) donated by BestPlant Co. (Curicó, Chile) were used in this study. One‐year‐old plants were transplanted to 2 l pots with Andisol soil and acclimated in a greenhouse (temperature: 25 ± 3°C; photoperiod: light 16/8 h dark; humidity: 60–70%; and a mean photosynthetic active radiation at midday of 300 μmol m −2 s −1 ) for 2 weeks as described previously in González‐Villagra et al (). Plants were then divided into two groups (20 plants for each group): daily irrigated (DI) and non‐irrigated (NI).…”
Section: Methodsmentioning
confidence: 99%
“…The DI plants were irrigated at field capacity; meanwhile, NI plants were exposed to water withholding to initiate drought stress. When NI plants were stressed [the 20th day of drought stress, based on previous study of González‐Villagra et al ], 100 μM Fluridone (Sigma, St. Louis, MO) was homogenously applied by spraying on a group of NI and DI plants (+FLU). After 24 h, in some cases, leaves were sprayed with a solution of 100 μM ABA (Sigma; +ABA).…”
Section: Methodsmentioning
confidence: 99%
“…In the Sardinian samples, anthocyanins seem to be almost equally distributed in the ethyl acetate, acetone, methanol, and water extracts, whereas in the Tunisian samples, the majority of anthocyanins were extracted by acetone. On the whole, Tunisian Cynomorium is richer in anthocyanins (p < 0.05), confirming the role of these chemicals in the prevention of drought stress [2]. In addition, the different extraction patterns suggest a different chemical composition in this phenolic sub-class.…”
Section: Total Antioxidant Power and Phenolics Contentmentioning
confidence: 68%
“…A 10 mg aliquot of each dried extracts was resuspended in 600 µL of D 2 1 H− 1 H total correlation spectroscopy (TOCSY) experiments were performed with a spectral width of 6000 Hz in both dimensions, an acquisition time of 0.171 s, a delay time of 1.0 s, number of scans of 128 and number of data points of 2048 (f2) and 256 (f1). TOCSY experiments were performed in phase-sensitive mode.…”
Section: Nmr Measurementsmentioning
confidence: 99%
“…Global climate change is modifying patterns of global precipitation, leading to changes in the frequency and magnitude of extreme climatic events, such as drought [1,2]. Increased drought enhances tree mortality [3,4] and influences ecosystem biodiversity as well as ecosystem structure and function [5][6][7][8]. Several studies have shown that terrestrial plants adapted and resistant to drought can alter their physiological characteristics to increase water use efficiencies to prevent death [9][10][11].…”
Section: Introductionmentioning
confidence: 99%